Palliative care consultation in patients with Staphylococcus aureus bacteremia. (April 2021) - Kobayashi, Takaaki; Salinas, Jorge L; Ten Eyck, Patrick; Chen, Benjamin; Ando, Tomo; Inagaki, Kengo; Alsuhaibani, Mohammed; Auwaerter, Paul G.; Molano, Ilonka; Diekema, Daniel J.
Background: Palliative care consultation has shown benefits across a wide spectrum of diseases, but the utility in patients with Staphylococcus aureus bacteremia remains unclear despite its high mortality. Aim: To examine the frequency of palliative care consultation and factors associated with palliative care consult in Staphylococcus aureus bacteremia patients in the United States. Design: A population-based retrospective analysis using the Nationwide Inpatient Sample database in 2014, compiled by the Healthcare Costs and Utilization Project of the Agency for Healthcare Research and Quality. Setting/subjects: All inpatients with a discharge diagnosis of Staphylococcus aureus bacteremia (ICD-9-CM codes; 038.11 and 038.12). Measurements: Palliative care consultation was identified using ICD-9-CM code V66.7. Patients' baseline characteristics and outcomes were compared between those with and without palliative care consult. Results: A total of 111, 320 Staphylococcus aureus bacteremia admissions were identified in 2014. Palliative care consult was observed in 8140 admissions (7.3%). Palliative care consultation was associated with advanced age, white race, comorbidities, higher income, teaching/urban hospitals, Midwest region, Methicillin-resistant Staphylococcus aureus bacteremia and the lack of echocardiogram. Palliative care consult was also associated with shorter but more expensive hospitalizations. Crude mortality was 53% (4314/8140) among admissions with palliative care consult and 8% (8357/10, 3180) among those without palliative care consult ( p < 0.001). Conclusions: Palliative care consultation was infrequent during the management of Staphylococcus aureus bacteremia, and a substantial number of patients died during their hospitalizations without palliative care consult. Given the reported benefit in other medical conditions, palliative care consultation may have a role in Staphylococcus aureus bacteremia. Selecting patients who may benefit the most should be explored.